Direktori Rumah Kos Putri di Sekitar Kampus Universitas Negeri Padang - Sasmi, Nia Anasta; Desriyeni, Desriyeni (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
In this paper discussed how to manufacture Directory boarding house Princess in Around Campus of the State University of Padang. This paper aims to determine the process of making Directory boarding house Princess in Around Campus Universitas Negeri Padang with the aim to develop and design a collection of library services in the form of a directory to make it easier to find information on homes that provide services rental house or boarding house for girls in around the campus of the State University of Padang. Methods of this paper is using descriptive method done with interview and collect data directly to the field, namely by visiting each boarding houses located around the campus of the State University of Padang. Based on analyzing the data, we can conclude that in the process of making the Directory boarding house Princess in Around campus State University of padang takes steps as follows: (1) collect data; (2) noted the existing data and then inputted into a Microsoft Word; (3) determine the subject; (4) the classification or grouping; and (5) the preparation of a directory.Keyword: Directories, boarding house, UNP.